Biochemical, Biophysical and Cellular Techniques to Study the Guanine Nucleotide Exchange Factor, GIV/Girdin. Issue 4 (7th December 2016) - Ghosh, Pradipta; Aznar, Nicolas; Swanson, Lee; Lo, I‐Chung; Lopez‐Sanchez, Inmaculada; Ear, Jason; Rohena, Cristina; Kalogriopoulos, Nicholas; Joosen, Linda; Dunkel, Ying; Sun, Nina; Nguyen, Peter; et al.
Abstract: Canonical signal transduction via heterotrimeric G proteins is spatiotemporally restricted, i.e., triggered exclusively at the plasma membrane, only by agonist activation of G protein‐coupled receptors via a finite process that is terminated within a few hundred milliseconds. Recently, a rapidly emerging paradigm has revealed a noncanonical pathway for activation of heterotrimeric G proteins via the nonreceptor guanidine‐nucleotide exchange factor, GIV/Girdin. Biochemical, biophysical, and functional studies evaluating this pathway have unraveled its unique properties and distinctive spatiotemporal features. As in the case of any new pathway/paradigm, these studies first required an in‐depth optimization of tools/techniques and protocols, governed by rationale and fundamentals unique to the pathway, and more specifically to the large multimodular GIV protein. Here we provide the most up‐to‐date overview of protocols that have generated most of what we know today about noncanonical G protein activation by GIV and its relevance in health and disease. © 2016 by John Wiley & Sons, Inc.